Analisis Distribusi Keterlambatan Kereta Angkutan Lebaran Tahun 2016 Pada DAOP 7 - Aghastya, Adya; Adi, Wahyu Tamtomo (Politeknik Perkeretaapian Indonesia Madiun, 2017)
This research aims to analyze delays at  railway  train  service, especially at DAOP 7 Madiun. Primary data  collection  is  done  through  observation  and  distribution  of  questionnaires. Observations were made to find out the actual departure time of train departure from the station compared to the time of departure plan. The survey results show that passengers can tolerate train  delays below 10 Minutes, and most (73%) can  not  tolerate  delays  longer  than  10  minutes.  Statistical descriptive results indicate that 49 percent of travel experiences  more  than  10  minutes delay, and delays vary between each train, the average delay is 16.29 minutes  with  a  standard deviation of 27.59  minutes. Results of delays data compared in various statistical distributions show the differences of each  train  delay  distribution,  dominated  by  logistics  distribution  and Weilbul, data of the curves show density curves tend to have skewness from standard normal distributions. The overall data  of  the  delay  is  most  closely  related  to   Weilbul's  distribution, although it can not be concluded with 95 percent confidence that the data  is  distributed  Weilbul. Further analysis by examining each train at the starting station to the final station  is  required to complete this delayed distribution review.